The Battery is the Message: Media Archaeology as an Energy Art Practice - Samir Bhowmik (ScholarWorks @ UMass Amherst, 2019)
This text is an investigation of battery technologies and planned obsolescence in the context of energy consumption, electronic waste and environmental crisis as brought on by current communication technologies. Tracing the battery’s formative histories, the text examines its messy chemistries, entanglements with portable computing to current extraction of constituent minerals of Lithium and Cobalt as bundled into contemporary media devices. Building on Hertz and Parikka’s Media Archaeology as an Art Method, the author aims to extend this research and critique into an energy art practice. Here, media archaeology becomes a method to conduct critical and artistic examinations of media technologies as concerned with energy and ecology. The text demonstrates this approach through the study of the Community Power Bank (2016-18), a community-participated energy art project in Helsinki. The project recycled Lithium-ion batteries through Do-It-Yourself (DIY) workshops, hacking and dismantling, and co-constructing power banks amidst discussion about e-waste and ecological concerns among community participants. The project also catalyzed conversations about the political economy of contemporary black-boxed technologies and the intertwined issues of energy, resource depletion and environmental impact.